Cefpodoxime Proxetil Floating Microspheres: Formulation and In VitroEvaluation: Formulation cefpodoxime proxetil floating microspheres - M.K. Deepa,; M. Karthikeyan, (Iranian Journal of Pharmaceutical Sciences, 2009)
The objective of the present study was to develop floating microspheres of cefpodoxime proxetil in order to achieve an extended retention in the upper GIT,which may result in enhanced absorption and the reby improved bioavailability. The microspheres were prepared by non-aqueous solvent evaporation method using polymers such as hydroxyl propyl methyl cellulose (HPMC K 15 M), ethyl cellulose in different ratios and cefpodoxime proxetil in each formulation.In vitro drug release were performed by USPapparatus type I and the microspheres were characterized by polymer compatibility by using FT-IR. The yield, particle size,Buoyancy percentage, drug entrapment efficiency, andin vitrodrug release werestudied. The result showed that microspheres yielded 50.5-72.2%. The particlesize was distributed between75-600 μm, drug entrapment efficiency was 14.1-28.2%, and Buoyancy percentage was 70.1-88.3%. The best drug release profiles were seen with formulation 2 at the ratio of drug to polymer of 1:2.